Software engineering : a practitioner$1 (Bs approach / s - Pressman, Roger S. (New York : McGraw-Hill Higher Education, 2010)
For almost three decades, Roger Pressman's "Software Engineering: A Practitioner's Approach" has been the world's leading textbook in software engineering. The new seventh edition represents a major restructuring and update of previous editions, solidifying the book's position as the most comprehensive guide to this important subject. The seventh edition of "Software Engineering: A Practitioner's Approach" has been designed to consolidate and restructure the content introduced over the past two editions of the book. The chapter structure will return to a more linear presentation of software engineering topics with a direct emphasis on the major activities that are part of a generic software process. Content will focus on widely used software engineering methods and will de-emphasize or completely eliminate discussion of secondary methods, tools and techniques. The intent is to provide a more targeted, prescriptive, and focused approach, while attempting to maintain "SEPA"'s reputation as a comprehensive guide to software engineering. The book will be organized in five (5) parts - Process, Modeling, Quality Management, Project Management, and Advanced Topics. The chapter count will remain at 32, unchanged from the sixth edition. However, eight new chapters have been developed and another six chapters have undergone major or moderate revisions. The remaining chapters have undergone minor edits/updates.
Software and Software Engineering -- Process Models -- Agile Development -- Principles that Guide Practice -- Understanding Requirements -- Requirements Modeling: Scenarios, Information, and Analysis Classes -- Requirements Modeling: Flow, Behavior, Patterns, and WebApps -- Design Concepts -- Architectural Design -- Component-Level Design -- User Interface Design -- Pattern-Based Design -- WebApp Design -- Quality Concepts -- Review Techniques -- Software Quality Assurance -- Software Testing Strategies -- Testing Conventional Applications -- Testing Object-Oriented Applications -- Testing Web Applications -- Formal Modeling and Verification -- Software Configuration Management -- Product Metrics -- Project Management Concepts -- Process and Project Metrics -- Estimation for Software Projects -- Project Scheduling -- Risk Management -- Maintenance and Reengineering -- Software Process Improvement -- Emerging Trends in Software Engineering -- Concluding Comment.
Includes bibliographical references (p. 871-888) and index.
1
Keywords: Software engineering